Local context influences memory for emotional stimuli but not electrophysiological markers of emotion‐dependent attention. (12th October 2017) - Barnacle, Gemma E.; Tsivilis, Dimitris; Schaefer, Alexandre; Talmi, Deborah
Abstract: Emotional enhancement of free recall can be context dependent. It is readily observed when emotional and neutral scenes are encoded and recalled together in a "mixed" list, but diminishes when these scenes are encoded separately in "pure" lists. We examined the hypothesis that this effect is due to differences in allocation of attention to neutral stimuli according to whether they are presented in mixed or pure lists, especially when encoding is intentional. Using picture stimuli that were controlled for semantic relatedness, our results contradicted this hypothesis. The amplitude of well‐known electrophysiological markers of emotion‐related attention—the early posterior negativity (EPN), the late positive potential (LPP), and the slow wave (SW)—was higher for emotional stimuli. Crucially, the emotional modulation of these ERPs was insensitive to list context, observed equally in pure and mixed lists. Although list context did not modulate neural markers of emotion‐related attention, list context did modulate the effect of emotion on free recall. The apparent decoupling of the emotional effects on attention and memory, challenges existing hypotheses accounting for the emotional enhancement of memory. We close by discussing whether findings are more compatible with an alternative hypothesis, where the magnitude of emotional memory enhancement is, at least in part, a consequence of retrieval dynamics.